Atrial septal defect closure is associated with a reduced prevalence of atrial tachyarrhythmia in the short to medium term: a systematic review and meta-analysis. Issue 22 (21st October 2010) - Vecht, Joshua A; Saso, Srdjan; Rao, Christopher; Dimopoulos, Konstantinos; Grapsa, Julia; Terracciano, Cesare M; Peters, Nicholas S; Nihoyannopoulos, Petros; Holmes, Elaine; Gatzoulis, Michael A; Athanasiou, Thanos
Abstract : Atrial tachyarrhythmias are a common complication of atrial septal defects. The objective was to determine the effect of atrial septal defect closure on pre-existing atrial tachyarrhythmias and to investigate if such an effect is present after either surgical or percutaneous closure. Medline, EMBASE, Cochrane Library, and Google Scholar databases were searched between 1967 and 2009. The search was expanded using the 'related articles' function and reference lists of key studies. All studies reporting pre- and post- closure incidence (or prevalence) of atrial tachyarrhythmias in the same patient groups were included. Data were independently extracted by two authors according to a pre-defined protocol. Incongruities were settled by consensus decision. Twenty six studies were identified including 1841 patients who underwent surgical closure and 945 who underwent percutaneous closure. Meta-analysis using a random effects model demonstrated a reduction in the prevalence of atrial tachyarrhythmias following atrial septal defect closure [OR = 0.66 (95% CI 0.57-0.77)]. This effect was demonstrated after both percutaneous [OR = 0.49 (95% CI 0.32-0.76)] and surgical closure [OR = 0.72 (95% CI 0.60-0.87)]. Immediate (<30 days) and mid-term (30 days - 5 years) follow-up also demonstrated a reduction in AT prevalence [ORs of 0.80 (95% CI 0.66-0.97) and 0.47 (95% CI 0.36-0.62) respectively]. Atrial septal defect closure, whether surgical or percutaneous, is associated with a reduction in the post-closure prevalence of pre-existing atrial tachyarrhythmias and atrial fibrillation in the short to medium term.